Ptolemaic military operations were a dominant factor in the spread of Egyptian cults across the early Hellenistic Aegean Sea - Glomb, Tomáš; Mertel, Adam; Pospíšil, Zdeněk; Stachoň, Zdeněk; Chalupa, Aleš (PloS one, 2018)
Early in the Ptolemaic era, Egyptian cults, particularly those of Isis and Sarapis, spread successfully to ports across the ancient Aegean Sea. Leading researchers in the field claim that the spread of these cults was influenced by multiple factors, ones that were mainly economic or political in character. However, the question of which factors had more weight or impact than others in the process of the early spread of Egyptian cults has not yet been answered in academic discussion. This could be related to the fact that the issue of the spread of religious innovations in the ancient Mediterranean has been addressed mainly by established historiographical methods such as the collection and critical analysis of archaeological and literary sources. Hypotheses and conclusions derived from these methods are, however, often unable to reflect the complexity of historical processes. A possible solution can be found in supplementing this established methodological apparatus by formalized methods, e.g. the coding of relevant datasets, statistics, geospatial modeling, and network analysis. To be able to compare the possible impacts of different factors on the spread of Egyptian cults in the Aegean Sea region, we 1) constructed a model of the ancient maritime transportation network as a platform for quantitative analysis, 2) transformed selected factors of possible influence into georeferenced parameters of the network, and 3) defined a mathematical model that allowed us to determine which parameters of the network explain the spatial dissemination of archaeological evidence connected to Egyptian cults. The results suggest that the most significant correlation is between the placement of Ptolemaic garrisons and the distribution of Egyptian temples and artefacts in the early Hellenistic Aegean Sea region. The interpretation would be that Egyptian military forces potentially played a significant role in the spread of Egyptian cults.
Keywords: Islands; Military Personnel; migrace lidstva; lodě; ozbrojené síly; Ships; vojenská zařízení; Military Facilities; vedení války; teoretické modely; Religion; starověký Egypt; History, Ancient; dějiny starověku; kultura; zásobování potravinami; Human Migration; Models, Theoretical; náboženství; lidé; Warfare; Humans; Food Supply; Culture; Egypt, Ancient; Mediterranean Sea; Středozemní moře; ostrovy